Securing the Future of Computer Science; Reconsidering Analog Computing. - Guzdial, Mark; Reed, Daniel (Communications of the ACM, 2013)
The article presents two blog posts posted on the organization's Website in 2011. One discusses computer science study and teaching in Great Britain. A lack of higher education programs in computer software development is discussed and attributed to national education standards requiring written examinations. A report by the scientific organization. The second blog post considers analog computers. The possibility that analog computing could be used as a supplement to digital computing is considered, with the concept of a hybrid computer employing both digital and analog computing discussed.